Toxicity Screening of Dibenzothiophene on Early Vertebrate Development - Memarshall, M. Ongkudon (Universiti Malaysia Sarawak (UNIMAS), 2015)
Dibenzothiophene is a minor component of petroleum crudes, coal tars, shale oil and synthetic fuels which has a toxic property to mammals and aquatic verterbrates. This research was conducted to analyse the toxicity effects of dibenzothiophene on zebrafish (Danio rerio) embryos at every pre determined stage of its embryogenesis. Different concentration of dibenzothiophene was exposed to the embryos and several parameters (developmental effects) were chosen to be observed throughout the embryogenesis of D. rerio embryos. The results of this experiment shows that dibenzothiophene cause delay in D. rerio embryos morphogenesis. LCso ofdibenzothiophene for D. rerio embryo was also determined in this study by taking the average total mortality of the replicates which has nearest value to 50%. It was concluded that different concentrations of dibenzothiophene exert different severity ofdefects in D. rerio embryogenesis.